Pemanfaatan Aplikasi Canva dalam Pengembangan Media Pembelajaran Interaktif Bahasa Arab untuk Anak Usia Dini: Utilization of Canva Application in the Development of Arabic Interactive Learning Media for Early Childhood - Fadlan Masykura Setiadi; Khairunnisa (Prodi Pendidikan Islam Anak Usia Dini Sekolah Tinggi Agama Islam Negeri Mandailing Natal- Sumatera Utara, 2025)
The digital age has brought significant changes in the development of learning media, especially for early childhood. Canva, with its ease of design and interactive features, offers great potential in creating innovative learning media. This article aims to explore the utilization of Canva in the development of Arabic interactive learning media for early childhood. Using a qualitative approach through in-depth interviews, observations, and questionnaires. This study aims to examine the effectiveness of Canva in creating learning materials that are interesting, relevant, and easily understood by early childhood. The results show that Canva is able to increase student engagement, motivate them to learn Arabic, and make it easier for teachers to design learning materials. This article also highlights the gaps in previous research, namely the lack of exploration of the use of Canva in the context of Arabic language learning and the need for media development that suits the characteristics of early childhood.